Teaching Management System with Applications of RFID and IoT Technology - Ping Tan; Han Wu; Peng Li; He Xu (MDPI AG, 2018)
Currently, Internet of Things (IoT) technologies are used in many areas, such as intelligent transportation, smart city, hospital, games, education. Earlier interactive response system uses infrared or radio frequency (RF) wireless communication technologies to transmit the students' answer to teachers' managerment system, where there exists high cost, inconvenient usage, difficult deployment. How to use IoT to improve the quality of higher education becomes a very important topic in the researh area of teaching. Radio Frequency Identification (RFID) is one of key technologies to implement IoT applications, and most of universities use the High Frequency (HF) RFID card as the students' identification devices in China. In this paper, a kind of WiFi supported RFID reader (WiRF) is implemented using open source hardware platforms, such as Node MCU and RFID-RC522. Then the proposed WiRF system is used to assist teacher to perform automatic attendance record and students' behavior record. In addition, Quick Response (QR) code is another technology to enable IoT. In this paper, QR code is designed to quickly access course video and perform real-time interactive response in the classroom, which will provide multidimensional learning and strengthen the motivation of students' learning. This IoT system can improve the attendance of students, and give a positive impact on students' learning process for higher education.